Multidimensional assessment of the European Energy Union: Integrating artificial intelligence and quantum fuzzy ranking approaches - Liu, Peide; Dinçer, Hasan; Yüksel, Serhat (My University, 2025)
The purpose of this study is to determine the significant indicators of European Energy Union policy. A novel artificial intelligence (AI)-enhanced and hybrid quantum fuzzy ranking approach are taken into consideration in this regard. There are three different stages in this hybrid model. The first stage includes the weighting the dimensions of the European energy union with AI-enhanced prioritization. The second stage consists of measuring the multidimensional performance for European energy union with artificial intelligence-enhanced ranking. In the final stage, the multidimensional performance for European energy union is evaluated by using quantum picture fuzzy rough sets based VIKOR methodology. The main contribution of this study is making a comparative evaluation with both artificial intelligence approach and fuzzy decision-making methodology. This situation provides an opportunity check the validity of the findings. In the analysis process, a novel artificial intelligence-based ranking methodology is proposed. Therefore, more effective evaluations can be conducted. The findings indicate that energy security, market functioning, and innovation have the best priorities. In case of maximum group utility, financial feasibility and technological infrastructure have the best ranking performance among the perspectives. The results with the highest maximum group utility are same with the priority results of the AI-enhanced ranking technique.
Keywords: Artificial Intelligence-Based Ranking; Picture Fuzzy Sets; Quantum Theory; Rough Sets; VIKOR